1998
DOI: 10.1021/es9700820
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Design Factors Influencing Free-Phase Hydrocarbon Cleanup

Abstract: Light nonaqueous phase liquid (LNAPL) saturation and movement in the subsurface are controlled by soil capillary characteristics, permeability, and fluid properties. Where free-product occurs in monitoring wells, LNAPL saturations in the formation vary significantly as a function of the observed thickness in the monitoring well and soil type. Fine-grained soils generally exhibit lower LNAPL saturations than coarse-grained material for the same observed thickness in a monitoring well. MAGNAS3 [MAGNAS3. HydroGeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It can be concluded that, given the same leak source, coarse-grained soil (sand) could cause a much larger LNAPL volume than fine-grained soils (silt F I G U R E 1 6 Influence of layering obtained through Series B4: vertical front depth and total light non-aqueous phase liquid (LNAPL) volume and clay). This is mainly attributed to the different intrinsic permeabilities of these soils, as explained by some previous researchers (Beckett & Huntley, 1998;.…”
Section: Influence Of Soil Type and Layering On Lnapl Flowmentioning
confidence: 58%
See 2 more Smart Citations
“…It can be concluded that, given the same leak source, coarse-grained soil (sand) could cause a much larger LNAPL volume than fine-grained soils (silt F I G U R E 1 6 Influence of layering obtained through Series B4: vertical front depth and total light non-aqueous phase liquid (LNAPL) volume and clay). This is mainly attributed to the different intrinsic permeabilities of these soils, as explained by some previous researchers (Beckett & Huntley, 1998;.…”
Section: Influence Of Soil Type and Layering On Lnapl Flowmentioning
confidence: 58%
“…For example, in the design of petrol and gas stations as well as industrial sites, heavy compaction is desired to control potential LNAPL contamination. Furthermore, soil type is generally considered in the studies on the flow and distribution of LNAPL (Beckett & Huntley, 1998; Lari et al., 2018; Oostrom & Lenhard, 1998). This is not sufficient because the porosity of a given soil can vary widely, depending on the geological history and loading path.…”
Section: Results Of Parametric Studies and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used Monte Carlo simulation to compare spatial moments of the LNAPL saturation in the plume where permeability was lognormally distributed and autocorrelated while constitutive relationships were also dependent on permeability. Beckett and Huntley [1998] examined different homogeneous soil classes, while Kaluarachchi [1996] included stochastic spatial variability of permeability in comparing recovery schemes with those which assume homogeneous conditions [ Cooper et al , 1995, 1998]. The model used by Kaluarachchi [1996] was a vertically averaged model, so only lateral heterogeneity was considered.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy 303 between different methods may be also due to poor well development or other 304 artifacts, as it has been documented in the case of comparisons between slug tests and 305 pumping tests in groundwater systems (Butler and Healey, 1998). The spatial scale of 306 the selected methods is determined by their radius of capture, typically larger for 307 coarser-grained sediments (Beckett and Huntley, 1998). 308 at research area B), although it showed higher LNAPL saturations and b n .…”
Section: Measurements and Calculations 267mentioning
confidence: 98%